To what extent does the presence of anonymity contribute to the fluctuations observed in cyberbullying behaviours demonstrated by students in higher education institutions in Saudi Arabia? - Alamr, Badr (2024)
Rapid improvements in technology, particularly in the communications industry, have caused a major evolution in the way individuals make contact, socialise and interact with one another. Unquestionably, these improvements have also had negative impact. Social media has contributed to the world by allowing the transfer of social communication from the real world into the virtual world. It should be acknowledged that social media has a great deal of benefit for individuals. The ease of social media use has helped individuals to connect with wider audiences anytime and anywhere. However, advancements in and features of social media can also lead to harmful effects, such as cyberbullying, which is the focus of this research. Bullying is a social issue in the real world that has shifted into cyberspace under the name ‘cyberbullying’. Previous research on cyberbullying has developed an understanding of such a problem, with some gaps that still need to be addressed. The overall research aim was to develop an understanding of cyberbullying causes in higher education students in Saudi Arabia. It should be taken into consideration that after this research started, universities moved their activities completely online because of Covid-19. This can motivate such research, as cyber-related work is likely to become increasingly important when working from home becomes the new normal.